Implementasi Pendekatan Pembelajaran Mendalam (Deep Learning) dalam Kurikulum Merdeka di SD Negeri 26 Mataram - Desinta; Darmiany; Radiusman (Mataram University, 2026)
This study aims to describe the implementation of the deep learning approach within the Kurikulum Merdeka at SD Negeri 26 Mataram. The research employed a descriptive qualitative approach with a phenomenological design involving two teacher participants, namely a lower-grade teacher and an upper-grade teacher. Data were collected through semi-structured interviews and analyzed using the Miles and Huberman flow model, which includes data reduction, data display, and conclusion drawing/verification. Data validity was ensured through time triangulation. The findings reveal both similarities and differences in the implementation of mindful, meaningful, and joyful learning principles across the stages of lesson planning, implementation, and evaluation. Similarities were found in analyzing students’ learning needs, applying differentiated instruction, connecting learning materials to students’ daily experiences, and providing formative feedback. Differences were identified in pedagogical focus: lower-grade teachers emphasized attention management, the use of concrete learning media, and strengthening basic literacy skills, while upper-grade teachers focused more on developing reflective and analytical thinking skills as well as exploring more complex learning concepts. Challenges in lower grades were related to early literacy skills and short attention spans, whereas in upper grades they were associated with the complexity of lesson planning and time management. Overall, the implementation of deep learning was adapted to the developmental characteristics of students at each grade level.